Military Sexual Trauma As a Risk Factor for Treatment Non-Response from an Online, Self-Management Posttraumatic Stress Disorder Treatment for Women Veterans - Chen, Jessica A. (Journal of interpersonal violence, 2024)
Women veterans are exposed to high rates of trauma, including military sexual trauma (MST), and face unique barriers to posttraumatic stress disorder (PTSD) treatment. Telehealth interventions that are tailored to women veterans’ unique lived experiences may improve treatment engagement and outcomes. It is important to ascertain how beneficial new telehealth interventions are in the context of different patient characteristics and trauma types, particularly for lower-intensity telehealth interventions (e.g., web-based programs or apps). This secondary analysis of a randomized clinical trial conducted in a sample of 102 women veterans examines predictors of treatment response to a self-management, telehealth intervention for PTSD: Delivery of Self Training and Education for Stressful Situations-Women Veterans (DESTRESS-WV). In the trial, women veterans with PTSD received either an online cognitive behavioral intervention with phone coaching, or phone monitoring alone. We examined associations between baseline patient characteristics (demographics, trauma types, and clinical symptoms) and treatment outcome at post-treatment, 3 months, and 6 months, focusing on the association between treatment outcome and MST. Our primary outcomes were changes in PTSD (PTSD Symptom Checklist, Version 5, PCL-5) and depression (8-item Patient Health Questionnaire, PHQ-8) in the full sample, adjusting for treatment condition. Women veterans who identified MST as the primary trauma for which they were seeking PTSD treatment experienced a nearly nine-point lesser improvement on the PCL-5 than those seeking PTSD treatment for other trauma types (e.g., childhood abuse, combat trauma; p = .0073). Similar patterns were found for depression symptoms. To our knowledge, this is the first study to examine the association between trauma type and treatment outcomes within the context of a self-management, telehealth treatment for PTSD. While the study was not powered to examine differential treatment response for patient subgroups, our exploratory findings suggest that gaps remain in providing effective PTSD care for women veterans who experienced MST.Trial registration: The trial and analysis plan were preregistered in ClinicalTrials.gov (Identifier: NCT02917447).